2022
DOI: 10.3390/cimb44070211
|View full text |Cite
|
Sign up to set email alerts
|

«Salivaomics» of Different Molecular Biological Subtypes of Breast Cancer

Abstract: The aim of the study was to determine the metabolic characteristics of saliva depending on the molecular biological subtype of breast cancer, as well as depending on the expression levels of HER2, estrogen receptors (ER), and progesterone receptors (PR). The study included 487 patients with morphologically verified breast cancer and 298 volunteers without breast pathologies. Saliva samples were obtained from all patients strictly before the start of treatment and the values of 42 biochemical indicators were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Another study by Bel’skaya et al . [ 63 ] found that there was no statistical difference of antioxidant activity in the different BC subtypes. According to previous literature, our results suggest that the anti-oxidative capacity is equivalent in different BC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Bel’skaya et al . [ 63 ] found that there was no statistical difference of antioxidant activity in the different BC subtypes. According to previous literature, our results suggest that the anti-oxidative capacity is equivalent in different BC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the presence in the saliva of elderly adults of under-oxidized productssubstrates of endogenous intoxication, formed, among other things, as a result of free radical processes [18]. The presence in the biological fluid of such compounds capable of acting as pronounced inhibitors of crystallization, and provides conditions for suppressing the formation of organo-mineral aggregates [18,19], described by visual assessment as crystalline elements [10].…”
Section: Methodsmentioning
confidence: 99%
“…To develop non-invasive diagnostic tests and discover new biomarkers for BC, classic omics-based strategies have allowed significant advances in blood/plasma-based omics. Salivaomics [ 28 ], urinomics, and milkomics have appeared as integrative omics that may develop a high potential for early diagnoses in BC. Thus, an analysis of the tumor circulome is considered a novel frontier in liquid biopsies.…”
Section: Introductionmentioning
confidence: 99%